Phenotypic Spectrum And Age Distribution of SLC25A4 Mutations - Finsterer, MD, PhD, Josef; Zarrouk-Mahjoub, PhD, Sinda (Journal of Medical Biomedical and Applied Sciences, 2018)
In a recent article, Thompson et al. reported about seven patients carrying the heterozygous mutations c.239G>A (4 patients) and c.703C>G (3 patients) in the SLC25A4 gene, clinically manifesting with severe mitochondrial DNA depletion syndrome1. All patients were born with respiratory insufficiency requiring artificial ventilation since birth1. We have the following comments and concerns.